Determination of the Genital Structures using Ultrasound in Canine Prenatal Fetuses - Chul-Ho Park; Ki-Seok Oh; Chang-Ho Son (The Korean Society of Animal Reproduction and Biotechnology, 2015)
The objective of this study was to evaluate the initial detection time and development of the fetal genital structures using ultrasound in twelve pregnant small bitches. The initial detection time of the fetal genital structures was as follows: genital tubercle at days 32.6; os penis at days 45.2; labia at days 45.7; scrotum at days 47.5. Ultrasonograms of fetal genital structure according to gestational stage were as follows: Undifferentiated stage (before day 35), the genital tubercle was observed to have a small elevation and just a hyper-echogenic structure in the midline between the umbilical cord and the tail in male and female fetus. Migration stage (between day 35∼45), the genital tubercle was observed as a hyper-echogenic, bilobular, oval shaped and the genital tubercle began to migrate from the initial position toward the umbilical cord in males, and toward the tail in females. Differentiated stage (after day 46), the penis and os penis were observed to stand out in the abdominal wall and the scrotum was observed toward the perineal region in male fetuses. The labia was detected at the base of the tail in female fetuses. These results indicate that ultrasound of fetal genital structures could be useful for fetal gender determination and a completely prepartum evaluation of the canine fetus.